Avaliação da segurança e eficácia "in vitro" da Cuscuta racemosa Martius - Bertoluci, Raquel Silveira [UNIFESP] (2017)
Cuscuta racemosa, Mart is a parasitic plant belonging to the family Convolvulaceae, known in Brazil for the popular synonymy of "cipó chumbo" and "yarn of eggs". It is popularly used for its anti-inflammatory and healing actions, applied to diuretic and digestive disorders and presents itself as an alternative of biodiversity for use in medicines and cosmetics. The present study verified the in vitro evaluation of the safety and efficacy of the Cuscuta racemosa extract for possible cosmetic and drug applications. Assays were carried out from crude extract and alkaloids fraction from Cuscuta racemosa to evaluate cytotoxicity, and phototoxicity, as well as determination of antimicrobial and antitumor activity. Cytotoxicity and phototoxicity assays were performed according to the standards recommended by the Organization for Economic Co-operation and Development (OECD) using 3T3 BALB cells. Microbiological analyzes were conducted with Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Candida albicans. The evaluation of antimicrobial activity was performed in liquid and solid media. Antitumor activity assays were performed with the HeLa, MDA-DB and Sk-Mel lines. Cytotoxicity tests revealed a cytotoxic effect of the crude extract at concentrations of 34.01 and 50 mg / mL, but at lower concentrations did not present significant action, indicating its safety for possible cosmetic and medicinal applications. Both samples tested showed no phototoxicity. The lethal dose estimated at 50% of the cells calculated for the crude extract was 352.25mg / kg. With respect to the antimicrobial activity, the samples did not present zone of inhibition in solid culture medium in the concentrations tested for none of the tested microorganisms. The crude extract was cytotoxic in all its concentrations in tumor lines. The results indicate the possibility of using the samples in cosmetics, since the alkaloid fraction showed absence of phototoxicity and absence of cytotoxicity, although the samples did not present significant antimicrobial in the concentrations tested. With respect to antitumor activity, complementary studies are necessary directing the active only to the place of action, minimizing the risks of performance of the extract in normal cells.